Glide of dislocations in <1 1 1>{3 2 1} slip system: an atomistic study. Issue 1 (2nd January 2016) - Terentyev, D.; Bakaev, A.; Van Neck, D.; Zhurkin, E. E.
Abstract: Atomistic calculations are performed to investigate plastic slip in the <1 1 1>{3 2 1} system in body-centred cubic iron. Several modern interatomic potentials, developed over the last decade, are applied to compute the stacking fault γ -line energy in the {3 2 1} plane and the results are compared with the ab initio prediction. The applied potentials have shown strong deviations, but several potentials acquired good qualitative agreement with the ab initio data. Depending on the applied potential, the lowest value of the Peierls stress for the edge dislocation (ED) is 50 MPa (Ackland and Bacon from 1997) and the highest is 550 MPa (Dudarev and Derlet from 2005), while for the screw dislocation it is much higher, in the range 1–2 GPa. At finite temperature, however, the flow stress of the ED is found to decrease exponentially reaching a negligible value at about 200 K, irrespective of the applied potential. On the basis of the data obtained using Ackland–Mendelev potential from 2004, we conclude that the slip resistance of the <1 1 1>{3 2 1} system is in between the resistance of the <1 1 1>{1 1 0} and <1 1 1>{1 1 2} slip systems.